Severe plastic deformation of Al–Zn alloys - Borodachenkova, Marina (2018)
In this work, the R&D work mainly focused on the mechanical and microstructural analysis of severe plastic deformation (SPD) of Al–Zn alloys and the development of microstructure–based models to explain the observed behaviors is presented. Evolution of the microstructure and mechanical properties of Al–30wt% Zn alloy after the SPD by the high–pressure torsion (HPT) has been investigated in detail regarding the increasing amount of deformation. SPD leads to the gradual grain refinement and decomposition of the Al–based supersaturated solid solution. The initial microstructure of the Al–30wt% Zn alloy contains Al and Zn phases with grains sizes respectively of 15 and 1 micron. The SPD in compression leads to a gradual decrease of the Al and Zn phase grain sizes down to 4 microns and 252 nm, respectively, until a plastic strain of 0.25 is reached. At the same time, the average size of the Zn particles in the bulk of the Al grains increases from 20 to 60 nm and that of the Zn precipitates near or at the grain boundaries increases as well. This microstructure transformation is accompanied at the macroscopic scale by a marked softening of the alloy. The SPD produced by HPT is conducted up to a shear strain of 314. The final Al and Zn grains refine down to the nanoscale with sizes of 370 nm and 170 nm, respectively. As a result of HPT, the Zn–rich (Al) supersaturated solid solution decomposes completely and reaches the equilibrium state corresponding to room temperature and its leads to the material softening. A new microstructure–based model is proposed to describe the softening process occurring during the compression of the supersaturated Al–30wt% Zn alloy. The model successfully describes the above–mentioned phenomena based on a new evolution law expressing the dislocation mean free path as a function of the plastic strain. The softening of the material behavior during HPT process is captured very well by the proposed model that takes into consideration the effects of solid solution hardening and its decomposition, Orowan looping and dislocation density evolution. In particular, it is demonstrated that the softening process that occurs during HPT can be attributed mainly to the decomposition of the supersaturated solid solution and, in a lesser extent, to the evolution of the dislocation mean free path with plastic strain.